Financialisation and illegal capital flight - Fine, Ben (Capitalism and economic crime in Africa, 2024)
For years illegal capital flight from South Africa has resulted in a staggering loss of wealth for the country. Below I investigate efforts to curb these flows of wealth. I argue that capital flight not only shifts resources elsewhere as is commonly presumed, it also shifts speculation elsewhere - capital flight is financialised.